2011
DOI: 10.1161/strokeaha.110.613000
|View full text |Cite
|
Sign up to set email alerts
|

Local Brain Temperature Reduction Through Intranasal Cooling With the RhinoChill Device

Abstract: Background and Purpose-Hypothermia is neuroprotectant but currently available cooling methods are laborious, invasive, and require whole-body cooling. There is a need for less invasive cooling of the brain. This study was conducted to assess the safety and efficacy of temperature reduction of the RhinoChill transnasal cooling device. Methods-We conducted a prospective single-arm safety and feasibility study of intubated patients for whom temperature reduction was indicated. After rhinoscopy, the device was act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…Although change of brain temperature was statistically significant, the achieved cooling rate is very low compared with alternative cooling methods already tested prehospitally. 8,17 Using intranasal cooling with the RhinoChill device, it was possible to reduce brain temperature by a mean of −0.53°C (SD, 0.24) in only 15 minutes, 17 which is significantly more than the decrease we found after 1 hour of surface head/neck cooling with the Sovika (mean, −0.32°C; SD, 0.2; P=0.012, please see Table and Small studies testing experimental active head cooling devices reported cooling rates of up to −0.6°C in deep (n=2 patients) and −1.84°C in superficial brain regions (−0.8 cm from cortex; n=8 patients). 9,10 Cold fluid circulating through these devices provides sustained heat exchange, but the need of an external liquid pump and electric power supply limits prehospital use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although change of brain temperature was statistically significant, the achieved cooling rate is very low compared with alternative cooling methods already tested prehospitally. 8,17 Using intranasal cooling with the RhinoChill device, it was possible to reduce brain temperature by a mean of −0.53°C (SD, 0.24) in only 15 minutes, 17 which is significantly more than the decrease we found after 1 hour of surface head/neck cooling with the Sovika (mean, −0.32°C; SD, 0.2; P=0.012, please see Table and Small studies testing experimental active head cooling devices reported cooling rates of up to −0.6°C in deep (n=2 patients) and −1.84°C in superficial brain regions (−0.8 cm from cortex; n=8 patients). 9,10 Cold fluid circulating through these devices provides sustained heat exchange, but the need of an external liquid pump and electric power supply limits prehospital use.…”
Section: Discussionmentioning
confidence: 99%
“…8,17 Moreover, the transient increases of blood pressure and ICP warrant caution when using the Sovika head and neck cooling device. As tympanic and bladder temperature do not reflect the actual brain temperature and tend either to over-or underestimate cooling effects, our study emphasizes that brain temperature monitoring is mandatory for evaluation of (new) cooling methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe respiratory failure as a result of ARDS and/or pneumonia may adversely affect cerebral oxygenation and brain energy metabolism, and contribute to secondary brain injury. It is unknown if regional methods of cooling using new devices such as intranasal cooling [25,26] will offer the neurological benefits of TTM with fewer systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 From a historical perspective, 47 years ago, Brown and colleagues produced a striking brain-body temperature gradient in canines by naso-oral perfusion and head immersion using cold saline as the hypothermic medium. 2 Within 20 to 38 minutes (median time, 32 minutes), intracerebral temperatures Ͻ20°C were reached with right atrial temperatures stabilizing between 30°C and 33°C.…”
mentioning
confidence: 99%